2010
DOI: 10.1111/j.1365-2842.2009.02056.x
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of the short‐ and long‐term changes in the condylar position following sagittal split ramus osteotomy (SSRO) with rigid fixation

Abstract: The purpose of this study was to compare the short- and long-term changes in condylar position related to the glenoid fossa, and skeletal and occlusal stability after orthognathic surgery. All of the study patients were assessed by cone-beam computed tomography images for condylar rotational changes and anteroposterior position in the pre-surgery, post-surgery and post-retention period. The condylar positions were evaluated on three planes: axial, coronal and sagittal. In the skeletal and occlusal measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 26 publications
4
55
0
2
Order By: Relevance
“…1 During surgery, the condylar axis rotates to maintain the intersegmental contact after the distal segment moves anteriorly or posteriorly. Kim et al 4 reported that in patients who had undergone SSRO with rigid fixation, the condyle showed an inward rotation on the axial plane and was positioned posteriorly, on the a Postgraduate student, Department of Orthodontics, School of Dentistry, Pusan National University Dental Hospital, Yangsan, South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…1 During surgery, the condylar axis rotates to maintain the intersegmental contact after the distal segment moves anteriorly or posteriorly. Kim et al 4 reported that in patients who had undergone SSRO with rigid fixation, the condyle showed an inward rotation on the axial plane and was positioned posteriorly, on the a Postgraduate student, Department of Orthodontics, School of Dentistry, Pusan National University Dental Hospital, Yangsan, South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…13 The rotation might be determined by many factors, including surgeon's experience, patient type, and time point of postoperative data. Some studies 8,14 evaluated the changes at 3 months after surgery; other studies [10][11][12][13] used the data 6 months after surgery. However, few studies evaluated condylar rotation changes immediately after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review of recent CBCT studies [12][13][14][15] regarding the positional changes in condyle after orthognathic surgery showed a significant change in condylar rotation by the surgery. However, few studies dealt with its contributing factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One is based on linear and angular measurements (Jung et al, 2009;Kim et al, 2010Kim et al, , 2011Park et al, 2012a) that apply the concepts used routinely in 2D cephalometry to 3D images. The second method is based on the use of iterative closest point algorithms (Cevidanes et al, 2007;Carvalho Fde et al, 2010;Almeida et al, 2011;Motta et al, 2011) that analyze the smallest displacements between two structures but do not take into account the shape being measured.…”
Section: Class III Surgical Evaluationsmentioning
confidence: 99%